Quartz oxygen isotopes from Tick Hill area in Mount Isa Inlier: indication of a regional fluid overprint. Issue 3 (3rd April 2022) - Le, T. X.; Dirks, P. H. G. M.; Sanislav, I. V.; Harris, C.; Huizenga, J. M.; Cocker, H. A.; Manestar, G. N.
Abstract: At the Tick Hill gold deposit, δ 18 Oquartz data for the mineralised lithologies and surrounding rocks are similar and fall within a narrow range of 10.5–13.7‰ V-SMOW. The highly mineralised quartzo-feldspathic mylonite has quartz δ 18 O (δ 18 Oquartz ) values of 11.3–13.6‰, which are similar to values for the surrounding rocks both locally and regionally, i.e. δ 18 Oquartz by itself does not provide a useful exploration tool. The δ 18 Oquartz values from the Tick Hill area most likely reflect the late Isan hydrothermal overprint at 1525–1520 Ma. The origin of the altering fluids is unclear, as the δ 18 Oquartz values overlap with reported δ 18 O values calculated for both metamorphic and igneous fluids. When combining the δ 18 Oquartz results with δ 18 Ocalcite results available from the literature, a temperature of 350–550 °C was calculated, which is consistent with observed alteration assemblages associated with gold mineralisation. KEY POINTS: The δ 18 Oquartz values (10.5–13.7‰ V-SMOW) of Au-rich quartz–feldspar mylonite are indistinguishable from the altered host rocks both local and regional. The narrow range of δ 18 Oquartz values for the rock units in the Tick Hill area and Mary Kathleen Domain most likely reflect a regional fluid overprint. The post-mineralised quartz–calcite veins yield higher δ 18 Oquartz values (14.1–17‰), possibly reflecting (partial) re-equilibration of minerals locally formed in late cataclastic fault rocks.